The Medical Student Wellbeing Workshop - Muhamad Saiful Bahri Yusoff; Ab Rahman Esa (Association of American Medical Colleges, 2012)
Abstract Introduction It is believed that through knowing one's own strengths, weaknesses, opportunities, and threats for improvement, an individual will improve and develop their capacity in dealing with changes and stressors. Developing self-improvement strategies based on one's own values, beliefs, capacity, and abilities can facilitate changes in a person. Researchers have found that the most practical and possible approach to manage stress is the self-change approach because it is within a persons control. The goal of this workshop is to help medical students handle stressors. Methods Over the course of this four-part workshop, relevant theoretical input related to stress, stressors, and coping strategies in the medical context will be discussed in order to allow participants to reflect on their personal strengths and weaknesses. Part one of this workshop involves a discussion on the importance of managing stress; the concepts of stress; the relationships between stress, stressors, and coping with stress; and, the impacts of unfavorable stress on individuals. Part two is dedicated to hands-on learning where participants are able to identify their individual stressors and coping strategies through simple psychometric assessments. Part three involves a group discussion where participants consolidate learning from the previous two sessions, and part four allows students to provide feedback and share their experiences. Results Students who participated in the workshop rated it positively as it helped them to increase their knowledge and awareness about their stress management skills. They were also able to develop their own strategies and approaches to study. In addition, evaluations on the impacts of this workshop on participants' mental health during a non-stressful and a stressful event were conducted. One evaluation found that there was a significant reduction of participant stress levels 4 months after the workshop. An additional evaluation found that those students who attended this workshop experienced less stress, anxiety, and depressive symptoms when compared to those who did not attend, which was sustained for 6 months. The results suggest the potential positive impacts of this workshop on the participants' mental wellbeing. Discussion The goal of this workshop is to help medical students in handling their stresses. Relevant theoretical input related to stress, stressors, and coping strategies in the medical context is discussed. Over the course of these discussions, medical students reflect on their personal strengths and weaknesses in order to learn practical techniques for managing stress.